34. Anatomical Pathology And Histopathological Changes Of Ascaridia Galli In Layer Chicken - Muhammad Hambal; Rizki Efriyendi; Henni Vanda; Rusli Rusli (Universitas Syiah Kuala, 2019)
This study aimed to determine the anatomical pathology and histopathological, and their relationship of the ascaridiosis caused by Ascaridia galli worms infection that have been found in layer chickens after necropsy, thus facilitating the diagnosis, treatment, and prevention of ascaridiosis. This study used 1 dead chicken from the Lambaro traditional market, Ingin Jaya District, Aceh Besar Regency. The sample was taken to the Pathology Laboratory, Faculty of Veterinary Medicine, Syiah Kuala University for dissected and observed in anatomical pathology changes, then histopathological preparations were made to observe histopathological changes. Data were obtained then analyzed descriptively and presented in the form of images. The results of anatomical pathology examination in chickens infected with ascaridiosis were found the Ascaridia galli worms infestation in the intestinal lumen with moderate infestation rates and focal area of hemorrhage in the intestinal mucosa. Then, histopathological examination were found desquamation of villous epithelium, hemorrhage in the intestinal mucosa, inflammatory cell infiltration, and proliferation of cryptic cells caused by A. galli worms infection. Based on the results of the examination concluded that there is an association between anatomical and histopathological pathology findings, namely hemorrhage in the intestine.